852 Complete Mesocolic Excision (CME) Versus Conventional Surgery for Colon Cancer: A Systematic Review and Metaanalysis. (4th May 2021) - Crane, J; Hamed, M; Borucki, J; El-Hadi, A; Shaikh, I; Stearns, A
Abstract: Introduction: Complete mesocolic excision (CME) lacks consistent data to advocate operative superiority compared to conventional surgery for colon cancer. We performed a systematic review and meta-analyses, analysing peri-operative, pathological, and oncological outcomes. Method: A systematic literature review was registered with PROSPERO and carried out using PRISMA guidelines. Outcomes reviewed included lymph node yield, R0, disease free and overall survival at five years. Results: 3039 citations were identified; 148 studies underwent full-text reviews and 34 matched our inclusion criteria. There were no significant differences between the CME and non-CME group in overall complications (13.8% vs.13.8%) or anastomotic leak (1.3% vs. 1.7%). Nodal yield was higher in the CME group, 18.7 compared to 13.6 in the non-CME group. The rate of R0 resection was 96.8% in CME compared to 95.5%. Overall survival at five years was higher in the CME group 77.8% compared to 69.7% in non-CME group. Conclusions: CME for colon cancer was associated with no significant differences in morbidity and mortality, better lymph node yield and R0 resection compared to the non-CME group. Our meta-analysis further supported this demonstrating an improved overall and disease-free survival at five years in the CME group compared to the non-CME group.